Role of chemotherapy alone or in combination with hyperthermia in the primary treatment of intraocular retinoblastoma: preliminary results. Issue 10 (1st October 1998) - Levy, C; Doz, F; Quintana, E; Pacquement, H; Michon, J; Schlienger, P; Validire, P; Asselain, B; Desjardins, L; Zucker, J M
Abstract : BACKGROUND: The efficacy of the etoposide-carboplatin combination in extraocular retinoblastoma is well known. This drug combination is therefore used in intraocular retinoblastoma, as primary reduction chemotherapy, before local treatment. The use of carboplatin in combination with diode laser hyperthermia as local treatment (thermochemotherapy) has been recently described as a conservative approach avoiding external beam radiotherapy in posterior pole tumours. METHODS: All patients were reviewed, who were treated for retinoblastoma at the Institut Curie between June 1994 and October 1995, in whom treatment included either reduction chemotherapy or thermochemotherapy or both modalities successively. 23 patients presenting with unilateral (three) or bilateral (20) intraocular retinoblastoma received neoadjuvant chemotherapy consisting of two courses of etoposide 150 mg/m 2 /day and carboplatin 200 mg/m 2 /day for 3 days. 15 patients (17 eyes), eight of whom had already received neoadjuvant chemotherapy, were treated by thermochemotherapy. RESULTS: Neoadjuvant chemotherapy: overall, seven eyes in seven patients could be treated conservatively, avoiding external beam irradiation, with a median follow up of 14 months. Thermochemotherapy: external beam irradiation was avoided for 14 of the 17 eyes treated. CONCLUSION: Integration of neoadjuvant chemotherapy and combined treatment with carboplatin and diode laser, into the therapeutic armamentarium for retinoblastoma allows use of more aggressive treatments such as enucleation and external beam radiation.